Comorbidity in children with rheumatic diseases: literature review and 10-year experience of own research - L.F. Bogmat; N.S. Shevchenko; T.O. Holovko; V.V. Nikonova; I.M. Bessonova; E.L. Akhnazariants; A.О. Fadieieva (Zaslavsky O.Yu., 2023)
Background. A decrease in the age of onset of rheumatic diseases in children, an increase in the total duration of the disease, the development of persistent functional and organic disorders of organs and systems determine the need to study comorbid conditions already in childhood in order to optimize their diagnosis and comprehensive therapy. The purpose was to study the frequency and main patterns for the formation and further progression of comorbidities in children with rheumatic diseases (juvenile idiopathic arthritis (JIA) and systemic lupus erythematosus (SLE)). Materials and methods. An analytical review of the literature on the prevalence and diagnosis of comorbid lesions in adult patients with rheumatic diseases and in children was carried out; 250 children aged 3-18 years with JIA and 67 children with SLE with a juvenile onset were dynamically monitored for the presence of comorbid conditions of the cardiovascular system, kidneys, lungs, eyes, bone tissue, blood lipid disorders. Results. The frequency and nature of comorbidity in children with JIA and SLE have been determined. Preservation of the process activity is the main factor in the progression of comorbid pathology and the formation of irreversible damage to organs and systems with the development of their failure and violations of the quality of life of patients. Conclusions. Based on the presented materials, it is possible to develop programs to prevent the formation and progression of irreversible damage to systems and organs that occur under comorbid conditions in children with rheumatic diseases and to effectively socialize these children.